Trauma Ultrasound in Civilian Tactical Medicine - Whelan, Lori; Justice, William; Goodloe, Jeffrey M.; Dixon, Jeff D.; Thomas, Stephen H. (Emergency Medicine International, 2012)
The term “tactical medicine” can be defined in more than one way, but in the nonmilitary setting the term tactical emergency medical services (TEMS) is often used to denote medical support operations for law enforcement. In supporting operations involving groups such as special weapons and tactics (SWAT) teams, TEMS entail executing triage, diagnosis, stabilization, and evacuation decision-making in challenging settings. Ultrasound, now well entrenched as a part of trauma evaluation in the hospital setting, has been investigated in the prehospital arena and may have utility in TEMS. This paper addresses potential use of US in the tactical environment, with emphasis on the lessons of recent years’ literature. Possible uses of US are discussed, in terms of both specific clinical applications and also with respect to informing triage and related decision making.